Chinese Short-Form Social Media Propaganda: A Case Study of the Communist Youth League's Douyin Content between November and December 2023 - Barrett, Kayla (My University, 2025)
Focusing on the popularity of the social media platform Douyin and its unique form of media content, this thesis aims to address research questions concerning contemporary ideotainment propaganda as it exists on the Chinese Communist Youth League’s official account. The research questions for this thesis are: (RQ1) As reflected on its official Douyin page, how does the CYL's contemporary ideotainment propaganda approach show its adaptability to its target audience of modern youth (ages 18-30) in an era of advanced technology and social media within the specific November-December 2023 timeframe; (RQ2) By analyzing the narrative elements present in its official Douyin content, how is modern online youth culture (language, artifacts, aesthetic, values, and other cultural expressions) reflected in the way that contemporary propaganda is formulated for social media, and is there an impact on the modern digital propaganda aesthetic when compared to traditional socialist realist styles; (RQ3) Using a combination of analysis methods, to what extent does the content on the CYL's official Douyin utilize traditional style propaganda themes as identified in the pilot (techno-nationalism, populism, historical narratives, progressive and advanced socialist China, and appeal to youth) and how does it compare to the thoughtwork guidelines presented by Mao Zedong in the May 1942 Talks at Yan’an Forum on Literature and Art. Employing a combination of qualitative and quantitative approaches, fifty of the CYL’s short-form videos uploaded between November and December 2023 were manually collected and examined for traditional Chinese-style propaganda themes, especially those as outlined in the May 1942 Yan’an Forum on Literature and Art. The thesis also looked for examples of additional propaganda art styles, such as Chinese-style socialist realism and the contemporary positive energy style. Through thematic, content, and descriptive statistical analyses, the study finds that the CYL utilizes a blend of traditional and modern digital techniques to generate propagandistic content that specifically appeals to young (aged 18-30) Chinese netizens. Propagandistic themes and styles were coded as either present or not based on the thematic and content analysis to find a percentage of occurrence. This analysis found that the themes were present at the following rates: 88% appeal to youth, 90% populism, 70% modern & progressive Socialist China, 66% techno-nationalism, 36% historical narratives, reflecting the CYL’s ability to combine traditional CCP propaganda techniques with contemporary propaganda mediums and methods like social media and user-generated style content (UGC) to create content that is both party-approved and appeals to the target audience. Additionally, the research concludes that the CYL’s Douyin still adheres to the guidelines for CCP thought work set by Mao Zedong at the Yan’an Forum in 1942. By incorporating modern digital artifacts and popular culture, it can be suggested that the CYL can modernize its content and appeal to both the Chinese youth and the CCP propaganda requirements. Finally, the results suggest that the CYL is increasingly able to fluently utilize youth culture to express the CCP’s political ideologies in an entertaining and digestible format on social media.
Keywords: Douyin, Chinese Communist Youth League, Propaganda, Digital Populism, Socialist Realism, Yan’an Forum on Literature and Art 1942